The impact of water as a security issue on the Middle East peace process: 1991-1996 - Kaniaru, Wanjiku (Rhodes University, Faculty of Humanities, Department of Political Studies, 1999)
In recent years, there has been increasing realisation that resource based conflicts constitute one of the most salient threats to the survival of mankind, namely, water. In particular, the fundamental link between water and security can no longer be ignored given the indispensable role of water in the sustenance of human life as well as crucial sectors of agriculture and industry. Since the flow of water does not respect political boundaries, co-operation in the utilisation of dwindling supplies remains the most sustainable option for the future in an era of ecological interdependence. This thesis endeavours to investigate the impact of water as a security issue on the Middle East peace process. This is done within the theoretical framework that is provided by the schools of complex interdependence and new security studies. With the demise of the cold war, and the emergence of an expanded security agenda, water is an important non-military threat especially in the Middle East region. However, even with an expanded security agenda, the case of the Middle East suggests that it remains difficult to discard the hierarchy of security issues advocated by the Realists. The ongoing debate between the schools of complex interdependence and Realism is instructive in determining whether co-operation over water issues, considered "low" politics, is attainable in the absence of resolving "high" politics concerns of territory and security. Given its profound security implications for the Middle East region, water has been accorded a central role in both the bilateral and multilateral peace negotiations. In the context of water scarcity, and rising demographic patterns, the role of water as a facilitator of regional co-operation remains critical. However, for multilateral co-operation over water resources to become a tangible reality, it is the contention of this thesis that both "low" politics issues of water and "high" polities concerns of territory as well as security must be addressed simultaneously.
Keywords: Middle East -- Politics and government -- 1979-|Arab-Israeli conflict, 1993- -- Peace|Water-supply -- Political aspects -- Middle East|Natural resources -- International cooperation